INNOVATIVE SCIENTIFIC-EDUCATIONAL CLUSTER AS A MECHANISM ACCELERATED INNOVATION PROCESS IN ICT - Usmonov, Botir (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article investigates the issues and challenges related to the variability, mobility of technologies of education, development of the conceptual framework based on modernization of IT education, formation of professional knowledge of future specialists of an IT profile in the system of continuous IT education in the conditions of the educational and scientific complex “school-college-university” and the ability IT expedient of such system of knowledge. The IT efficiency of the system of professional knowledge could be achieved through a scientific justification of the project-creative component that is not investigated enough. And there is necessity to implement this experimental innovative component of the professional IT training.In the process of the research the author worked out a theoretical cluster system model of economy by applying innovative technologies where intersubjective innovative connections are available. The research results involve clarification of the following concepts essence “modernization of the system of professional knowledge in IT” and “future specialists in the sphere of ITs”; introduction of a project- creative approach in an educational-scientific complex “an IT - school with its specialization – an IT - college – an IT-university” under conditions of the IT education.